How far is Covid-19 Pandemic Situation Influence Surgical Treatment in Gynecology Cancer? : Comprehensive Review for Indonesian - Syamel Muhammad; Restu Susanti (Andalas Obstetrics And Gynecology Journal, 2020)
Corona virus disease 2019 (COVID-19) was declared as global pandemic and caused devastating crisis in society. Despite of the growing pandemic, high quality medical services toward gynaecologic oncology patients must continue without overlooking the safety of medical staffs. Reducing risk is crucial and achieved by limiting high risk situations. The decision to perform or postpone surgery should be made based on the type and stage of the disease, medical condition of the patient, area census of COVID-19 cases, COVID-associated risks, and available logistic support including adjuvant treatment services. There are several recommendation for gynaecology cancer treatment published by several countries. However, those guidelines cannot be applied to every country across the globe because of the different situations of COVID-19 therefore we proposed guidelines for Indonesia. Surgical management for confiermed COVID-19 case should be postponed for at least 15 days for nonemergency cases. Surgery must be performed immediately for emergency cases such as Haemorrhage with unstable vital status refractory to transfusion, viscus perforation, signs of bowel obstruction refractory to conservative treatment, closed loop bowel or large bowel obstruction, hydatiform mole for live saving procedure.  Keywords: COVID-19, gynaecology cancer, surgical management